Pengetahuan Ibu Hamil Trimester III tentang Perawatan Payudara di Klinik Pratama Bina Sehat Kasihan, Bantul, Yogyakarta - Luvita Sari; Susi Ernawati (Alma Ata University Press, 2015)
There are many breastfeeding mothers who suffer from mastitis and nipples blister. The nipples blister happened because the condition of a nipple who rarely cleaned and incorrect position when breastfeeding. To get the succeed in breastfeeding, breast care regularly during pregnancy will conduct the increase of milk production. The purpose of this study was to know the knowledge level of pregnant women about breast care. There was an observational study with quantitative descriptive design. The populations were 250 of pregnant women third trimester at the Clinic Pratama Bina Sehat in November 2014–Januari 2015. The samples were 71 women selected by random sampling tecniques and data were analysed by univariat analysis. The results showed that most of pregnant women in third trimester at the Clinic Pratama Bina Sehat Kasihan Bantul Yogyakarta aged 20-35 year (70.4%), graduated from senior high school (53.5%), housewife (60.6%) and having the parity of even multipara (47.9%). The level of knowledge of third trimester pregnant women about breast care based on age, education, occupation and parity were 68.0%, 63.2%, 69.8%, 61.8% that were included in medium category. In conclusion, the knowledge levels of pregnant women about breast care at Clinic Pratama Bina Sehat were in medium category.